2021
DOI: 10.1093/jxb/erab001
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and water deficit-induced changes in hydraulic properties and xylem anatomy of tomato fruit and pedicels

Abstract: Xylem water transport from the parent plant plays a crucial role in fruit growth, development, and the determination of quality. Attempts have been made to partition the hydraulic resistance of the pathway over the course of development, but no consensus has been reached. Furthermore, the issue has not been addressed in the context of changing plant and fruit water status under water deficit conditions. In this study, we have conducted a rigorous investigation into the developmental changes that occur in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…VXW determined by dye infusion technique represents xylem functionality of shoots to cavitation and challenges. Xylem inflow delivers essential minerals such as calcium to the fruit, leaf and other tissues Li et al, 2021) and the dye infusion technique may be used to determine early diagnosis of calcium deficiency. Furthermore, this technique could be used to determine bud dormancy release studies.…”
Section: Resultsmentioning
confidence: 99%
“…VXW determined by dye infusion technique represents xylem functionality of shoots to cavitation and challenges. Xylem inflow delivers essential minerals such as calcium to the fruit, leaf and other tissues Li et al, 2021) and the dye infusion technique may be used to determine early diagnosis of calcium deficiency. Furthermore, this technique could be used to determine bud dormancy release studies.…”
Section: Resultsmentioning
confidence: 99%
“…Here we investigate the distribution of xylem vulnerability among reproductive and vegetative tissues in a herbaceous annual to determine the hydraulic priority of reproductive tissues relative to vegetative tissues under water‐limiting conditions. Domesticated tomato was selected as a well‐documented test species with an annual life history (although the ancestral species are likely to have been more perennial in growth habit) and large reproductive water requirements (Bertin, 2003; Bussières, 1994; Li et al, 2021; Shameer, Vallarino, Fernie, Ratcliffe, & Sweetlove, 2020; Van Ieperen, Volkov, & Van Meeteren, 2003). We hypothesize that fruit growth will be hydraulically prioritized during drought through higher resistance to xylem cavitation in the stem and reproductive water supply (peduncle) compared with leaves (lamina and petiole), and that fruit growth may be maintained even during water stress by drawing on water provided by the capacitance and cavitation of less resistant tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In oriental pear Wonhwang, quick enlargement of xylem and phloem tissues in pedicel by GA treatment during the fruit development resulted in the increased size of the fruit ( Park and Park, 2017 ), which was consistent with the results in our study, and this process was primarily due to the increment of cell division of both xylem and phloem. In tomato, Li et al (2021) found that the water deficit did not change the hydraulic resistance and the vascular structure in the pedicel; however, this could not provide any clue about how the structural differences of vascular affect the hydraulic transport in the plant. A mutant tomato ( hws-1 ) with wider phloem and narrower xylem rings showed a higher sugar concentration in the phloem exudates and a higher Brix level in the fruit, indicating that the increased phloem area ratio contributes to the higher fruit Brix in tomatoes ( Lombardo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 83%
“…Various anatomical techniques have been applied to study the structural properties of pedicel including grape ( Knipfer et al, 2015 ), apple ( Drazeta et al, 2004 ; Horbens et al, 2015 ), tomato ( Rančić et al, 2010 ; Li et al, 2021 ), litchi ( Song W. et al, 2018 ; Song W. P. et al, 2018 ), and pepper ( Setiamihardja and Knavel, 1990 ), indicative of the importance of pedicels to the fruit development and growth. However, there have been limited studies combing various anatomical techniques to study the function of the pedicel ( Rančić et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%